The Role of Artificial Intelligence in Enhancing MSME Performance: The Interplay Between Customer Orientation, Competitor Orientation, and Brand Commitment - Intan Rahma Dewi; Muhammad Ikko Oktaviano; Wildan Arief Firdaus; Puji Endah Purnamasari; Ditya Permatasari (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to examine the impact of customer orientation, competitor orientation, and brand commitment on the business performance of Micro, Small, and Medium Enterprises (MSMEs), focusing on the moderating role of artificial intelligence (AI) in enhancing strategic responsiveness and competitiveness in the digital transformation era.Method: A quantitative explanatory approach was used, involving structured questionnaires distributed to 373 MSME owners and managers in Lowokwaru District, Malang City. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess both direct and moderating effects. Reliability and validity tests were performed through composite reliability and average variance extracted (AVE) analysis.Result: We found that customer orientation, competitor orientation, and brand commitment significantly and positively influenced MSME performance. However, AI did not significantly moderate these relationships, indicating that AI adoption among MSMEs is still in the early stages and has not yet shown measurable effects. Despite this, AI adopters exhibited improved operational efficiency and decision-making accuracy.Practical Implications for Economic Growth and Development: The study highlights the need for MSMEs to strengthen customer focus, competitor awareness, and brand commitment to enhance business performance. Although AI did not show a moderating effect, gradual adoption of AI technologies could improve efficiency, innovation, and competitiveness, fostering regional economic growth.Originality/Value: This research contributes to the literature by integrating AI as a moderating variable in the relationship between marketing orientation and business performance, offering empirical evidence that extends AI-based strategic capability models within the MSME context.